Strengthening of Sharia Savings, Loans, and Financing Cooperative Institutions: Friedman's Legal System Theory Framework - Yunita, Ani; Budi Santoso; Agus Sarono; Weni Hawariyuni (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to strengthen the Sharia Savings and Loans and Financing Cooperatives (KSPPS) institution from the perspective of legal system theory inIndonesia. Thisstudy employs anempiricaljuridical research type, utilizing a qualitative approach. The research used primary and secondary data sources. The research findings indicate that strengthening KSPPS institutions from the perspective oflegal system theory, including structural elements, is crucial for enhancing human resource capacity and fostering synergy among KSPPS supervisory institutions. Legal structure enhancement can be achieved by improving the performance of the Sharia Supervisory Board and the National Sharia Council in overseeing KSPPS, as well as establishing internal supervisory units and a Sharia Islamic deposit insurance agency. Furthermore, the strengthening of KSPPS BMT institutions can also be realized by synergizing with organizations such as the Ministry of Cooperatives, the Financial Services Authority, the National Sharia Council, and the Sharia Supervisory Board. This strengthening will contribute to the formulation of legislation related to KSPPS. With the institutional strengthening of KSPPS, institutional issues related to KSPPS, in terms of legal substance, legal structure, and legal culture, can be minimized and more easily resolved